THE DUAL BENEFITS OF HIGH-INTENSITY INTERVAL TRAINING: IMPROVING COGNITION AND REDUCING BODY WEIGHT IN SCHIZOPHRENIA PATIENTS ON RISPERIDONE - Fachruddin, Ismi Irfiyanti; Asmi, Nur (Universitas Airlangga, 2025)
This quasi-experimental study investigated the effects of High-Intensity Interval Training (HIIT) on weight loss and cognitive function in patients with schizophrenia treated with risperidone. Conducted at Dadi Regional Special Hospital, South Sulawesi, Indonesia, the study included 40 participants who met the inclusion criteria, including males aged 20–40 years, with disease onset of fewer than five years, and receiving risperidone therapy (4–6 mg/day). The exclusion criteria included severe organic comorbidities and recent substance use. The participants were divided into treatment and control groups, with the former undergoing 30 HIIT sessions over 10 weeks. Each session lasted 25 min, incorporating warm-up, core HIIT, and cool-down phases, with heart rates monitored to ensure anaerobic intensity (80–90% of maximum heart rate). The results showed a significant weight reduction in the treatment group (mean decrease: 0.475 kg, p < 0.001), indicating the potential of HIIT to mitigate risperidone-induced weight gain. Cognitive performance, assessed via the Schizophrenia Cognitive Rating Scale (SCoRS v BI), improved in both groups, with no significant differences between them (p > 0.05). However, greater improvement was observed in the treatment group. This study supports the integration of HIIT as adjunct therapy for schizophrenia, offering the dual benefits of cognitive enhancement and weight management. Further research incorporating genetic factors and advanced monitoring tools is needed to refine these findings.